Optimalisasi Pengelolaan Dana Zakat, Infak Dan Sedekah (ZIS) Perspektif Good Corporate Governance (GCG) Di Nu Care-Lazisnu Purbalingga - Hana Adzkiya; Ubaidillah (CV. ALIM'SPUBLISHING, 2023)
The importance of managing zakat, infaq and alms funds makes the government continue the empower by issuing various laws and regulations on zakat management so that to be objectives of ZIS managemen can be optimized. But in reality, until now with many institutions that manage zakat and various provisions that have been set have not been able to reach the potential of zakat in Indonesia, this can be caused by on obstacle in managing each institution. One of the obstacles experienced by NU CARE-LAZISNU Purbalingga in managing zakat, infaq and alms funds is the lack of strategy used in collecting and distributing ZIS funds. Therefore, this study aims to find out how to manage ZIS funds and how to optimize the management of ZIS funds from a GCG perspective at NU CARE-LAZISNU Purbalingga. This research uses descriptive qualitative method, using collecting data by observation thecniques, interviews and document at NU CARE-LAZISNU Purbalingga. Data validation thecniques use source triangulation, technical triangulation and time triangulation. Data analysis techniques using data reduction, data presentation and conclusion/verification. The results showed that the management of ZIS funds carried out by NU CARE-LAZISNU Purbalingga is quite good but there is still a need for evaluation and improvement so that it can fulfil the UU No. 23 year 2011 and SKKNI and on optimizing the management of ZIS funds from a GCG perspective at NU CARE-LAZISNU Purbalingga is not optimal.